Identification of ACA‐28, a 1′‐acetoxychavicol acetate analogue compound, as a novel modulator of ERK MAPK signaling, which preferentially kills human melanoma cells. (9th May 2017) - Satoh, Ryosuke; Hagihara, Kanako; Matsuura, Kazuki; Manse, Yoshiaki; Kita, Ayako; Kunoh, Tatsuki; Masuko, Takashi; Moriyama, Mariko; Moriyama, Hiroyuki; Tanabe, Genzoh; Muraoka, Osamu; Sugiura, Reiko
Abstract : The extracellular signal‐regulated kinase (ERK) signaling pathway is essential for cell proliferation and is frequently deregulated in human tumors such as melanoma. Melanoma remains incurable despite the use of conventional chemotherapy; consequently, development of new therapeutic agents for melanoma is highly desirable. Here, we carried out a chemical genetic screen using a fission yeast phenotypic assay and showed that ACA‐28, a synthetic derivative of 1′‐acetoxychavicol acetate (ACA), which is a natural ginger compound, effectively inhibited the growth of melanoma cancer cells wherein ERK MAPK signaling is hyperactivated due to mutations in the upstream activating regulators. ACA‐28 more potently inhibited the growth of melanoma cells than did the parental compound ACA. Importantly, the growth of normal human epidermal melanocytes (NHEM) was less affected by ACA‐28 at the same 50% inhibitory concentration. In addition, ACA‐28 specifically induced apoptosis in NIH/3T3 cells which were oncogenically transformed with human epidermal growth factor receptor‐2 (HER2/ErbB2), but not in the parental cells. Notably, the ACA‐28‐induced apoptosis in melanoma and HER2‐transformed cells was abrogated when ERK activation was blocked with a specific MEK inhibitor U0126. Consistently, ACA‐28 more strongly stimulated ERK phosphorylation in melanoma cells, as compared in NHEM. ACA‐28 might serve as a promising seed compound for melanoma treatment. Abstract : Our chemical genetic screen identified ACA‐28, a 1′‐acetoxychavicol acetate (ACA) analogue compound as a MAPK signaling modulator. ACA‐28 induced apoptosis in melanoma and NIH/3T3 cells oncogenically transformed with HER2//ErbB2 by stimulating ERK phosphorylation. ERK inhibition antagonized the ACA‐28‐induced apoptosis and cytotoxicity.